Associations Between Follicular Fluid Biomarkers and IVF/ICSI Outcomes in Normo-Ovulatory Women—A Systematic Review - Soha Albeitawi; Saif-Ulislam Bani-Mousa; Baraa Jarrar; Ibrahim Aloqaily; Nour Al-Shlool; Ghaida Alsheyab; Ahmad Kassab; Baha’a Qawasmi; Abdalrahman Awaisheh (Biomolecules)
(1) Background: The follicular fluid (FF) comprises a large portion of ovarian follicles, and serves as both a communication and growth medium for oocytes, and thus should be representative of the metabolomic status of the follicle. This review aims to explore FF biomarkers as well as their effects on fertilization, oocyte, and embryo development, and later on implantation and maintenance of pregnancy. (2) Methods: This review was registered in the PROSPERO database with the ID: CRD42025633101. We parsed PubMed, Scopus, and Google Scholar for research on the effects of different FF biomarkers on IVF/ICSI outcomes in normo-ovulatory women. Included studies were assessed for risk of bias using the NOS scale. Data were extracted and tabulated by two independent researchers. (3) Results: 22 included articles, with a sample size range of 31 to 414 and a median of 60 participants, contained 61 biomarkers, including proteins, growth factors, steroid and polypeptide hormones, inflammation and oxidative stress markers, amino acids, vitamins, lipids of different types, and miRNAs. Most of the biomarkers studied had significant effects on IVF/ICSI outcomes, and seem to have roles in various cellular pathways responsible for oocyte and embryo growth, implantation, placental formation, and maintenance of pregnancy. The FF metabolome also seems to be interconnected, with its various components influencing the levels and activities of each other through feedback loops. (4) Conclusions: FF biomarkers can be utilized for diagnostic and therapeutic purposes in IVF; however, further studies are required for choosing the most promising ones due to heterogeneity of results. Widespread adoption of LC-MS and miRNA microarrays can help quantify a representative FF metabolome, and we see great potential for in vitro supplementation (IVS) of some FF biomarkers in improving IVF/ICSI outcomes.